Effect of Occupational Health and Safety on Employee Performance in the Ghanaian Construction Sector - Moses Segbenya; Esi Yeboah (SAGE Publishing, 2022)
The contribution of the construction sector to the socio-economic development of Ghana cannot be underestimated. However, these benefits are not without challenges such as frequent industrial accidents and diseases leading to the loss of lives of workers and or influencing employee and organisational performance. Construction firms are therefore required to ensure workers' health and safety at the construction sites. This study therefore explores the influence of occupational health and safety (OHS) on construction workers' performance in Ghana. This study employed the descriptive research design from the quantitative approach, and a sample of 120 employees was drawn out of 200 workers from the sector. Means, standard deviations and multiple standard regression were used to analyse the data. The study found that OHS policies in the construction sector had a statistically significant effect on employee performance and related well with best international practices. However, the construction sector lacks regular health and safety induction, orientation and refresher courses for construction workers. Hence there were still occupational accidents and diseases affecting workers in the sector. For fear of being sacked, workers hardly report pains and injuries suffered at the construction sites. Also, construction workers felt that the high cost of training could explain why employers were not providing regular refresher training and induction training on OHS in the workplace. The study, therefore, concluded that more efforts were required from the management of construction firms than workers, as opposed to the position of Heinrich Domino's theory, to ensure occupational safety and health in the sector. It was recommended that the management of construction companies in the sector should prioritise the health and safety of workers over the economic concern with regard to the cost of training.